UPLC-QTOF/MS tentative identification of phytochemicals from Vernonia amygdalina Delile acetone and ethanol leaf extracts - Christeldah Mkhonto; Vusani Makananise; Idowu J. Sagbo; Madonna N. Mashabela; Peter T. Ndhlovu; Bongani P. Kubheka; Wilfred Otang-Mbeng (AOSIS, 2023)
Background: Vernonia amygdalina Delile is a woody medicinal plant that is commonly used in various folklore medicine in South Africa against helminthic, protozoal and bacterial infections. Despite its high medicinal values, the chemical profile of this plant has not been fully elucidated and remains unclassified. Aim: The present study reports the tentative identification of untargeted metabolite profiling from V. amygdalina Delile acetone and ethanol leaf extracts. Setting: The study took place in the Nkomazi municipality which is located in the eastern part of the Ehlazeni district municipality of the Mpumalanga province. Methods: Metabolites were identified using ultraperformance liquid chromatography (UPLC) method coupled with quadrupole time of flight mass spectrometry (qTOF/MS). Results: The UPLC-qTOF-MS analysis tentatively revealed the presence of prominent metabolites, 17 of which were identified in acetone extracts and 12 in the ethanol extracts of V. amygdalina Delile. The identified metabolites included compound classes such as terpenoids which were highest in the acetone extracts (23.53%) and flavonoids which were highest in the ethanol extracts (25%). Conclusion: The findings reveal several significant bioactive compounds which may contribute to the development of new antifungal drugs. Contribution: The results showed significant chemical differences between both extracts of the plant in the profiles. The findings revealed several significant bioactive compounds which may contribute to the development of new antifungal drugs.